Preventing early marriage in North Lampung Regency: An analysis of the efforts of the Ministry of Religion's Office - Zahrani, Sabina Siti; Nurmayani, Nurmayani; Deviani, Eka (Goodwood Publishing, 2022)
Purpose: The aim of this research is to analyze the efforts of the North Lampung Regency Ministry of Religion's Office to prevent early marriage and the factors that hinder North Lampung Regency’s efforts to prevent early marriage. Research methodology: Qualitative analysis was used. Field studies involve collecting data or information directly from the Office of the Ministry of Religion of North Lampung Regency and KUA related to the topic or problem you want to research. In conducting field studies, researchers carry out direct observations, collect samples or data, interview informants, and record data. Results: The efforts made by the North Lampung Regency Ministry of Religion Office should be more diverse, and it is hoped that outreach will not only be carried out within the community, but will focus more on schools. Limitations: There are several factors that hinder the efforts of the North Lampung Regency Ministry of Religion to prevent early marriage. Starting with promiscuity, which cannot be avoided and is not balanced with sufficient understanding, people do not clearly know the impact of promiscuity, which results in early marriage. Contributions: The prevention of early marriage requires active community participation. Community participation in preventing early marriage can involve education about the risks and consequences of marriage at a young age, sexual education, and the promotion of gender equality.